Striving with grace : views of free will in Anglo-Saxon England - Kleist, Aaron J. (Toronto Old English series, 2008)
"The question of whether or not our decisions and efforts make a difference in an uncertain and uncontrollable world had enormous significance for writers in Anglo-Saxon England. Striving with Grace looks at seven authors, who wrote in either Latin or Old English, and the ways in which they sought to resolve this fundamental question"--Provided by publisher.